2020
DOI: 10.1021/acs.jpcc.0c00369
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Electron-Withdrawing/-Donating Groups on the Sensitizing Action of the Novel Organic Dye “3-(5-(4-(Diphenylamino)styryl)thiophen-2-yl)-2-cyanoacrylic Acid” for N-Type Dye-Sensitized Solar Cells: A Theoretical Study

Abstract: Computational studies using density functional theory and time-dependent DFT approaches have been performed to study a series of metal free donor−π-linker–acceptor (D−π–A) dyes. Taking the novel organic D5 dye (3-(5-(4-(diphenylamino)­styryl)­thiophen-2-yl)-2-cyanoacrylic acid) as the primary structure, with triphenylamine as the donor, cyanoacrylic acid as the acceptor, and a thiophene group as the π-linker, we have studied the effect of the substitution of different electron-withdrawing and electron-donating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 92 publications
0
29
0
Order By: Relevance
“…Our calculated results demonstrated that such a natural dye have a high electron injection efficiency and also a longer excited state lifetime but the regeneration efficiency and the charge recombination efficiency are also higher which negatively impacts on the efficiency of the dye. As discussed in our previous articles, [25][26][27][28][29]35,38 the ΔG regen is a more decisive factor than the ΔG inject as the electron injection is a very fast process whereas regeneration is a much slower. As ΔG regen has an adverse effect on the efficiency, so in this case the efficiency is low as observed in the experiments.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…Our calculated results demonstrated that such a natural dye have a high electron injection efficiency and also a longer excited state lifetime but the regeneration efficiency and the charge recombination efficiency are also higher which negatively impacts on the efficiency of the dye. As discussed in our previous articles, [25][26][27][28][29]35,38 the ΔG regen is a more decisive factor than the ΔG inject as the electron injection is a very fast process whereas regeneration is a much slower. As ΔG regen has an adverse effect on the efficiency, so in this case the efficiency is low as observed in the experiments.…”
Section: Resultsmentioning
confidence: 90%
“…The IPCE also depends on the driving force for the electron injection from the excited state of the dye to the semiconductor that is, the ΔG inject that has been calculated previously by our group in previous articles. [28][29][30] The complete computational details are given in Data S1. The regeneration efficiency (ΔG regen ) and the excited state lifetimes (τ) are also important parameters, which are calculated in this article based on our previous literatures.…”
Section: Computational Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, the hole is injected from the dye to the highest occupied molecular orbital (HOMO) of the photocathode and the hot electron is transferred from the dye to the redox or catalytic agent. 13,14 In the operation of the DSSC, undesired electron transfer Figure 1: Schematic presentation of the processes occuring in p-DSSC solar cell of a photoactive complex coupled to a PPV polymer.…”
Section: Introductionmentioning
confidence: 99%
“…a hydrogen evolution catalyst, instead to a redox agent, such as I − 3 /I − . 11,13,16,18 Furthermore, apart from just addressing the properties of the DSSCs, hole conducting organic polymers have been put forward as viable alternatives to NiO or other metal oxide materials, as the tuning of the physicochemical properties of polymers is easier 19 than those of NiO.…”
Section: Introductionmentioning
confidence: 99%